Improving Student Learning Outcomes on Theme 4 Sub-Theme 1 Learning I Class 2nd Semester I SDN Kebandungan Through Interactive Video Media Online Thematic Learning - Andi Pranoto (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this study was to improve student learning outcomes in thematic learning in grade II SD. This research is a classroom action research (PTK) which is conducted in three cycles, each cycle consisting of planning, implementation, observation, and reflection stages. The subjects of this study were 10 class II students of SDN Kebandungan for the 2020/2021 academic year. Data collection techniques using observation and tests. Data analysis includes data reduction, data presentation, and drawing conclusions. Research shows that the use of interactive instructional video media can improve student learning outcomes in the subject matter of Theme 4 Sub Theme 1 Learning 1 about determining the flat segment in class II semester I SDN Kebandungan academic year 2020/2021 as evidenced by the percentage of completeness of learning outcomes in cycle I 60% to 80% in cycle II and to 100% in cycle III.